The Effect of Corporation Social Responsibilities on Information Asymmetry and Profit Variance (Fluctuation) in the Accepted Corporations in Tehran Stock Exchange - Rad, Nasrin Sedighi; Mosavi, Sayed Mir Bakhsh Kamrani (International Journal of Economics and Financial Issues, 2017)
Scandal and downfall news of financial corporations and big institutes such as; Aron, Arthur Anderson, and Verledkam in the beginning of the 21th century indicate unmoral and irresponsible commercial policies observations in term of social dimension. Moreover, the effect of corporations on society has been known as a world problem and beneficiaries` expectances of commercial units roles are increasing. Attention to the corporations` effects in society has caused existence of newfound and important concept in literature policy as social responsibility and corporations consistencies. The research aim is investigating the effect of corporation social responsibilities on information asymmetry and profit variance (fluctuation) in the accepted corporations in Tehran Stock Exchange. Based on the research aim, investigating the effect of corporation social responsibilities on information asymmetry and profit variance (fluctuation), two hypotheses have been introduced to analyze 148 accepted corporations ` data of Tehran Stock Exchange by systematic deletion from 2011 to 2015. Research regression model has been tested by paneling data methodology and constant effect policy. Information asymmetry and profit fluctuation are dependent variables and corporation social responsibilities are independent variables. Research methodology is descriptive and measuring, the research is applicational based on its aim and is post eventual in term of its events. Research conclusions express the existence of corporations' social responsibilities meaning effect on information asymmetry for the first hypothesis. Moreover, the existence of this effect on profit fluctuation is confirmed for the research second hypothesis. So, this research is recognized as proving hypotheses in accounting job about positive relationships between corporations` social responsibility and many economic agencies. Keywords: corporation social responsibility, information asymmetry, profit fluctuation (variance) JEL Classification: M14